Ochrona patentowa procesu technologicznego jako decyzja finansowa - Gryko, Józefa Monika (Patent Protection of Technological Process as Financial Decision, 2006)
The article is concerning usefulness of patent protection of new technological solution in innovative firms. It states that patenting technological process is one of methods of preventing imitation. The decision how to protect innovation against imitation should be treated as a financial decision. It depends on the cash flows generated or protected by legal protection of the new process. There are advantages and disadvantages of patenting technological process and they have an influence on both size and volatility of cash flows generated by commercial use of innovation. Only comparison of expenditures on effective legal protection and profits from it can give an answer if the patent protection is the best way of preventing imitation.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1109, s. 247-256